Abrus precatorius Leaf Extract Stimulates Insulin-mediated Muscle Glucose Uptake: In vitro Studies and Phytochemical Analysis - Lankatillake, Chintha; Huynh, Tien; Dias, Daniel A (Planta Medica, 2024)
Diabetes mellitus, linked with insulin resistance and hyperglycaemia, is a leading cause of mortality. Glucose uptake through glucose transporter type 4, especially in skeletal muscle, is crucial for maintaining euglycaemia and is a key pathway targeted by antidiabetic medication. Abrus precatorius is a medicinal plant with demonstrated antihyperglycaemic activity in animal models, but its mechanisms are unclear.This study evaluated the effect of a 50% ethanolic (v/v) A. precatorius leaf extract on (1) insulin-stimulated glucose uptake and (2) related gene expression in differentiated C2C12 myotubes using rosiglitazone as a positive control, and (3) generated a comprehensive phytochemical profile of A. precatorius leaf extract using liquid chromatography-high resolution mass spectrometry to elucidate its antidiabetic compounds.A. precatorius leaf extract significantly increased insulin-stimulated glucose uptake, and insulin receptor substrate 1 and Akt substrate of 160 kDa gene expression; however, it had no effect on glucose transporter type 4 gene expression. At 250 µg/mL A. precatorius leaf extract, the increase in glucose uptake was significantly higher than 1 µM rosiglitazone. Fifty-five phytochemicals (primarily polyphenols, triterpenoids, saponins, and alkaloids) were putatively identified, including 24 that have not previously been reported from A. precatorius leaves. Abrusin, precatorin I, glycyrrhizin, hemiphloin, isohemiphloin, hispidulin 4′-O-β-D-glucopyranoside, homoplantaginin, and cirsimaritin were putatively identified as known major compounds previously reported from A. precatorius leaf extract.A. precatorius leaves contain antidiabetic phytochemicals and enhance insulin-stimulated glucose uptake in myotubes via the protein kinase B/phosphoinositide 3-kinase pathway by regulating insulin receptor substrate 1 and Akt substrate of 160 kDa gene expression. Therefore, A. precatorius leaves may improve skeletal muscle insulin sensitivity and hyperglycaemia. Additionally, it is a valuable source of bioactive phytochemicals with potential therapeutic use for diabetes.
Keywords: Abrus precatorius; Fabaceae; diabetes mellitus; LC-HRMS; hyperglycaemia; GLUT4